2021
DOI: 10.1016/j.copsyc.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Leaving religion: deconversion

Abstract: Religious change was an important theme in the psychology of religion from its beginning with a focus on conversion, but with the emergence of new religious movements and the recent growth of religious unaffiliation, religious exiting and deconversion received growing attention. This review evaluates recent progress in deconversion research by the inclusion of key psychological constructs, such as personality, values, attachment, prosociality, well-being, religious socialization and development, and by an enga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 32 publications
(23 reference statements)
1
34
1
4
Order By: Relevance
“…Research suggests some negative association between neuroticism and religiosity, though the link is not consistent across cultures (Saroglou, 2017). Furthermore, people who exit from religion have occasionally been found to be high in neuroticism (Streib, 2021) and insecure in their attachment (Granqvist & Kirkpatrick, 2016), but other research suggests that both deconverts and socialized nonbelievers are more neurotic compared to religious believers (Saroglou et al, 2020). The difference in aspects of emotional stability and well-being occasionally found between believers and nonbelievers is typically explained in terms of the social support believers benefit from the community (Hayward & Krause, 2014).…”
Section: Personality and Cognitive Characteristicsmentioning
confidence: 99%
“…Research suggests some negative association between neuroticism and religiosity, though the link is not consistent across cultures (Saroglou, 2017). Furthermore, people who exit from religion have occasionally been found to be high in neuroticism (Streib, 2021) and insecure in their attachment (Granqvist & Kirkpatrick, 2016), but other research suggests that both deconverts and socialized nonbelievers are more neurotic compared to religious believers (Saroglou et al, 2020). The difference in aspects of emotional stability and well-being occasionally found between believers and nonbelievers is typically explained in terms of the social support believers benefit from the community (Hayward & Krause, 2014).…”
Section: Personality and Cognitive Characteristicsmentioning
confidence: 99%
“…In addition, recent research has revealed that religious deconversion has increased over the years (Streib, 2021). Interestingly, despite no longer identifying as religious, these “religious nones” still exhibit a religious residue wherein they report religious emotions, attitudes, and behaviors more consistent with currently religious individuals than never religious individuals (e.g., Van Tongeren et al, in press).…”
Section: Mental Health Symptomsmentioning
confidence: 99%
“…There is extensive literature on people who "deconvert," i.e., who turn away from their religious tradition, and who either find another one or leave the religious field for good (see, for an overview, Steppacher et al 2022;Enstedt et al 2019a;Streib 2021). Enstedt and colleagues state in their introduction to their edited volume that while conversion (i.e., turning toward a new religion) is rather well-researched, the process of deconversion still needs more attention, especially regarding the aspect of what is carried along from one's former denomination, which is a crucial point since " [b]ehaviours rooted in moral codes and religious teachings (especially if they have been adopted at a young age) tend to colour the life of the individual even though he or she has taken a new path" (Enstedt et al 2019b, p. 3).…”
Section: Previous Research and Theoretical Considerationsmentioning
confidence: 99%